The 2020 Twitter Hack – So Many Lessons to Be Learned - Paul D. Witman; Scott Mackelprang (Journal of Cybersecurity Education, Research & Practice)
In mid-July 2020, the social media site Twitter had over 100 of its most prominent user accounts start to tweet requests to send Bitcoin to specified Bitcoin wallets. The requests promised that the Bitcoin senders would receive their money back doubled, as a gesture of charity amidst the COVID-19 pandemic. The attack appears to have been carried out by a small group of hackers, leveraging social engineering to get access to internal Twitter support tools. These tools allowed the hackers to gain full control of the high-profile user accounts and post messages on their behalf. The attack provides many paths for investigation into the prevention, response, and impacts of cybersecurity breaches.